Effects Of Microsoft Mathematics 4.0 On Prospective Mathematics Teachers' Computational Thinking And Learning Motivation - Rafika Meiliati; Dima Marillah; Fitri; Achmad Salido; Aswin; Dayana Sabila Husain (Koordinat Jurnal MIPA, 2026)
This study aimed to examine the effect of Microsoft Mathematics 4.0 on prospective mathematics teachers’ computational thinking (CT) skills and learning motivation in learning functions. A quantitative approach with a quasi-experimental one-group pre-test–post-test design was employed, involving 17 first-semester mathematics education students at Universitas Sembilanbelas November Kolaka. The participants were prospective mathematics teachers who studied the topic of functions using Microsoft Mathematics 4.0 as an interactive learning tool. Data were collected using CT tests and learning motivation questionnaires and analyzed using descriptive statistics, the Shapiro–Wilk normality test, and paired-samples t-tests. The results revealed a statistically significant improvement in students’ CT skills (t(16) = −5.33, p < 0.05) and learning motivation (t(16) = −13.93, p < 0.05) after learning functions with the support of Microsoft Mathematics 4.0. These findings suggest that integrating interactive mathematical software in learning functions can effectively enhance both students’ computational thinking and their learning motivation